Migration Experience and Access to a First Job in Uganda - Delphine Boutin (Institute for the Study of Labor (IZA), 2016)
Does experiencing internal migration hasten the access to the labour market? This paper provides an answer by studying the gap in transition length to a first job between young people in Uganda that have ever migrated inside the country and never-migrants of the same age category. To take into the account the specific context of Uganda (some enters at a very young age, other before the end of school and other have never attended school), different starting points of transition are considered: from the date of birth, from the minimum legal age (14 years old) and from the date of school exit. Extended proportional hazards models shows that transition duration is shorter for migrants than for non-migrants (except for the school-to-work transition), although effects vary considerably according to the area of origin and destination and the reasons for migration. Decomposition in durations' gap reveals the importance of unobservable factors, especially the role of area of origin, gender, age cohort and access to education.
Keywords: J15; J61; J64; 330; internal migration; school-to-work transition; job search; youth employment